Sapikul Sagendhongan: The Value of Javanese Traditional Heritage in The Practice of Islamic Heritage Distribution in Klaten Community Indonesia - Saputro, Muhammad Andi; Zuhdi, Syaifuddin; Yusuf, Jibrail Bin (Universitas Muhammadiyah Surakarta, 2025)
This study examines the value of Javanese customary heritage in inheritance distribution in the Jatinom community, Klaten, focusing on applying customary law and its conformity with Islamic heritage law. The research analyzes the “Sapikul Sagendhongan” inheritance system and explores social and cultural factors affecting inheritance distribution. This study utilized a socio-legal approach and employed qualitative analysis through in-depth interviews with four respondents and examination of related legal documents. Results show that the Jatinom community consistently implements an inheritance distribution system that gives a more significant portion to male heirs than women, with a 2:1 ratio, primarily due to the perception that men have greater family responsibilities. While Javanese customary law remains dominant, there is an adaptation to Islamic law principles in inheritance distribution. Cultural factors, such as family values and cooperation traditions, play a significant role. The Jatinom community is committed to maintaining cultural values while respecting religious provisions. This study provides new insights into the interaction between local traditions and broader legal norms in Javanese society, confirming that Javanese customary law and Islamic law can operate harmoniously in inheritance distribution, ensuring cultural preservation without violating religious principles. The research contributes to understanding the complex dynamics of inheritance practices in Indonesia, highlighting the importance of considering local customs in legal frameworks.